Molecular Diagnosis and Antibodies Tests for Brucellosis Detected in Aborted and Apparently Healthy Sheep and Goats in and around Al Bayda City, Libya - Ahmed Altalhy; Khalid Shukri (AlQalam Journal of Medical and Applied Sciences, 2024)
The goal of the current research was to evaluate antigen and antibody reaction’s method in comparison with real time PCR for detection of brucella agent in sheep and goat. Therefore, seven hundreds and twenty-eight blood and milk samples were isolated from sheep and goats apparently healthy and suspected brucellosis brought to the Veterinary Clinical Complex from areas in and around Al Bayda, Libya. Blood samples were subjected to serological tests including Rose Bengal Plate Technique (RBPT), Enzyme-linked immunosorbent test (ELISA) for detection of IgA, IgM and also milk ring test to detect the antibodies of brucella agent. Also, the samples subjected by Real Time PCR to determine the presence of bcsp31 gene (Brucella gen). Out of the total examined samples (133) 18.26%, (139) 19.09%, (3) 0.41% and (126) 17.3% were tested positive by RBPT, ELISA IgG, IgM and Real Time PCR respectively. specificity and Sensitivity of RBPT compared with real- time PCR were 98.9% and 79.59% respectively. While, sensitivity and specificity of ELISA for IgG with Real Time PCR were 79.59% and 100% respectively, while, for ELISA IgM were 6.12% and 100% respectively. In conclusion, we suggest using Real Time PCR as a supplementary test in the diagnosis of brucella disease and as a confirmatory test in suspicious cases. الهدف من هذه الدراسة هو تقييم الاختبارات التي تعتمد علي التفاعل بين الاجسام المضادة و الانتجين مقارنة بجهاز تفاعل البلمرة المتسلسل ذو الوقت الحقيقي لتشخيص مرض البروسيلا في الاغنام والماعز. لذلك سبعة مائة وثمانية وعشرون عينة دم تم جمعها من حيوانات سليمة ظاهريا وكذلك نفس العدد عينات حليب سحبت من نفس الحيوانات. المشتبه أصابتها بالبروسيلا والمشخصة من العيادات البيطرية في وحول منطقة البيضاء. ليبيا. عينات الدم تم اختبارها بواسطة الاختبارات السيرولوجيه والتي تشمل اختبار لوحة بنقال, الاليزاIgG, IgM وكذلك اختبار حلقة الحليب للكشف عن وجود الاجسام المضادة للبروسيلا. وكل عينات الدم تم اعادة فحصها بواسطة تفاعل البلمرة المتسلسل ذو الوقت الحقيقي لتحديد وجود جين bcsp31 (جين البروسيلا). وكانت النتائج كالتالي 133)18.26%, (139)19.09%, (3) 0.41% و(126)17.3% علي التوالي. خصوصيه وحساسية اختبار لوحة بنقال مقارنة بتفاعل البلمرة المتسلسل ذو الوقت الحقيقي كانت 98.9%, 79.59% علي التوالي في حين حساسية و خصوصيه الاليزا IgG مع بتفاعل البلمرة المتسلسل ذو الوقت الحقيقي 79.59% و100% علي التوالي اما الاليزا IgM فكانت 6.12% و100% علي التوالي. الخلاصة نقترح استخدام تفاعل البلمرة المتسلسل ذو الوقت الحقيقي في تشخيص مرض البروسيلا كاختبار تأكيدي للحالات المشتبه بها